EFEK HEPATOTOKSISITAS KEMOTRAPI TERHADAP PASIEN KANKER PARU BUKAN SEL KECIL: TINJAUAN PUSTAKA SISTEMATIS - Junita Septiana Pasaribu, (2022)
Lung cancer is the number one cause of cancer death in Indonesia. Non-small cell lung cancer is the most common type of lung cancer found in most patients. There are various kinds of procedures that can be used to treat this disease, one of the treatments that are often and commonly used at this time is chemotherapy. Platinum-based chemotherapy treatment are the most often treatment used for nonsmall cell lung cancer. Along with its efficacy, there are side effects that can interfere with its effectiveness in the treatment of lung cancer. One of the side effects is hepatotoxicity. This study aims to analyze the hepatotoxicity effect of non-small cell lung cancer patients using platinum-based hemotherapy treatment. This systematic review research conducted by collecting journals that are appropriate to the inclusion criteria from the PubMed, Science Direct, and Google Scholar databases in the 2011-2021 publication period. Two journals were included in this study. Both of the journals agree that there is an association between the incidence of hepatotoxicity. the incidence of hepatotoxicity in patients using platinum-based chemotherapy treatment often occurs at a mild stage